A geometria no curso de Pedagogia a distância do acordo Brasil-Japão : conhecimentos para a docência mobilizados na formação inicial - Moreno, Heliete Martins Castilho (2014)
The paper entitled "The Geometry in Pedagogy Course of distance the Agreement Brazil - Japan: knowledge for teaching mobilized in the initial training" resulted from research conducted in the post-Graduation Program in Education, in line de Science Education and Mathematics Education of University Federal de Mato Grosso (UFMT) with the Group of Studies and Research in Mathematics Education (GRUEPEM). The interest in knowing what are the contributions that holding the area of Mathematics offers academics to carry out their teaching duties in the early years of elementary school arises from the first participation as a trainer currently teaching pedagogy of distance at UFMT the eight offerings made. Having the general objective "to investigate the knowledge in teaching Geometry, mobilized by academics of the Education Course of distance the Agreement Brazil-Japan", chose a qualitative approach, based on Bogdan and Biklen (1994) and interpretive analysis method with content analysis according to Bardin (2011) and Laville (1999) to answer the research problem: What skills for teaching were mobilized with the geometry shown in the initial course of Pedagogy distance of the agreement Brazil-Japan? To produce information were used remarks from the academic foruns boards that discussed matters of geometry throughout the area, on the reports of internship in geometry after the completion in Mathematics area and Course Conclusion Paper (CCP). Data were analyzed using the theory of Garcia (1999) on teacher training, supported by Tardif (2003) and Shulman (1986). Freitas and Bittar (2004), Nacarato (2001), Nacarato and Passos (2003) and Lorenzato (2006) contributed to the topics on teaching mathematics. Psycho pedagogic, content, didactic content and context: the components of professional knowledge proposed by García (1999) were used as categories of analysis. The subjects were selected from the classification of internship reports, which resulted in five academics who were trainee in Geometry in Brazilian Schools in Japan, in elementary school, who have Pedagogy as superior first training and who contributed at least once in each of the analyzed forums. The analysis points to the mobilization by academics, during the development of the area of mathematics at the Pedagogy Course of distance of Brazil-Japan agreement, the four components of knowledge for teaching pointed out by García (1999). We believe that by the nature of the documents themselves analyzed, the most current category on the forums was the Knowledge Content, while the reports of internship was Didactic Content Knowledge and on course conclusion paper was the Psycho pedagogic Knowledge. The Knowledge Context appears very little in the CCP, doesn’t appear on the forums, but it is mobilized in internship reports with an appreciable extent.